SINERGI LEMBAGA KEUANGAN SYARIAH DAN UMKM DALAM PENGUATAN INKLUSI KEUANGAN DI INDONESIA - Muhamad Abdul Gofur; Farah Naila Mufidah; Naela Soraya (Taksasila Edukasi Insani, 2025)
This study aims to explore the linkages between Sharia Financial Institutions (SHIs) and Micro, Small and Medium Enterprises (MSMEs) in improving financial inclusion in Indonesia. Using a descriptive qualitative method based on a literature review, this study found that LKS plays a vital role in offering financing based on sharia principles that are suitable for the nature of MSMEs. In addition, LKS also provides financial training, business guidance, and management and spiritual support. The approach of digitalization, utilization of Islamic social funds, and creation of local partnerships has proven successful in reaching MSMEs that are not yet connected to formal financial institutions. However, challenges such as low understanding of Islamic finance and the limited network of LKS are still obstacles in maximizing this synergy. Therefore, cooperation between the government, LKS, and MSME players is essential to build an inclusive and sustainable Islamic economic ecosystem.Keywords: financial inclusion, Islamic financial institutions, Islamic financing, MSMEs